Highly Efficient and Stable Self‐Powered Mixed Tin‐Lead Perovskite Photodetector Used in Remote Wearable Health Monitoring Technology. Issue 5 (9th December 2022) - Liu, Fengcai; Liu, Kai; Rafique, Saqib; Xu, Zengyi; Niu, Wenqing; Li, Xiaoguo; Wang, Yifan; Deng, Liangliang; Wang, Jiao; Yue, Xiaofei; Li, Tao; Wang, Jun; et al.
Abstract: Realization of remote wearable health monitoring (RWHM) technology for the flexible photodiodes is highly desirable in remote‐sensing healthcare systems used in space stations, oceans, and forecasting warning, which demands high external quantum efficiency (EQE) and detectivity in NIR region. Traditional inorganic photodetectors (PDs) are mechanically rigid and expensive while the widely reported solution‐processed mixed tin‐lead (MSP) perovskite photodetectors (PPDs) exhibit a trade‐off between EQE and detectivity in the NIR region. Herein, a novel functional passivating antioxidant (FPA) strategy has been introduced for the first time to simultaneously improve crystallization, restrain Sn 2+ oxidization, and reduce defects in MSP perovskite films by multiple interactions between thiophene‐2‐carbohydrazide (TAH) molecules and cations/anions in MSP perovskite. The resultant solution‐processed rigid mixed Sn–Pb PPD simultaneously achieves high EQE (75.4% at 840 nm), detectivity (1.8 × 10 12 Jones at 840 nm), ultrafast response time ( t rise / t fall = 94 ns/97 ns), and improved stability. This work also highlights the demonstration of the first flexible photodiode using MSP perovskite and FPA strategy with remarkably high EQE (75% at 840 nm), and operational stability. Most importantly, the RWHM is implemented for the first time in the PIN MSP perovskite photodiodes to remotely monitor the heart rate of humans at rest and after‐run conditions. Abstract : A novel functional passivating antioxidant strategy is introduced to simultaneously improve crystallization, restrain Sn 2+ oxidization, and reduce defects in mixed tin‐lead (MSP) perovskite films. This work highlights the first flexible photodiode using MSP perovskite with remarkable performance. Finally, the remote wearable health monitoring (RWHM) is implemented for the first time in the PIN MSP perovskite photodiodes to remotely monitor the heart rate of humans.